Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2010
DOI: 10.3233/nre-2010-0579
|View full text |Cite
|
Sign up to set email alerts
|

Family-to-Family Link Up Program: A community-based initiative supporting families caring for someone with an acquired brain injury

Abstract: Introduction: The Family To Family Link Up Program (f2f Link Up) is a pilot program aimed to promote connections between families who have a family member with an Acquired Brain Injury. Methods: A total of 46 families participated in the program coordinated by The Bouverie Centre in Melbourne Victoria. Link-Ups, involving one or several sessions with members from two or more families. Link-Ups were conducted by Victorian metropolitan and regional ABI workers who were trained as Link-Up facilitators. A co-opera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 27 publications
1
5
0
Order By: Relevance
“…Some of these interventions had specific names (e.g. the ‘Family-to-Family Link Up Program’ (f2f Link Up) provided by Butera-Prinz 11 and colleagues), whereas others were reported on in more general terms (e.g. the ‘outpatient social work liaison programme’ provided by Albert 7 and colleagues).…”
Section: Secondary Aimsmentioning
confidence: 99%
See 1 more Smart Citation
“…Some of these interventions had specific names (e.g. the ‘Family-to-Family Link Up Program’ (f2f Link Up) provided by Butera-Prinz 11 and colleagues), whereas others were reported on in more general terms (e.g. the ‘outpatient social work liaison programme’ provided by Albert 7 and colleagues).…”
Section: Secondary Aimsmentioning
confidence: 99%
“…In order of frequency (with number of studies in brackets), the top three factors reported with a negative caregiving outcome for the traumatic brain injury cohort were: high levels of caregiver burden (17); poor family functioning (16); and poor mental health and high levels of caregiver emotional distress (11). For the spinal cord injury cohort, the top three factors reported were: high levels of caregiver burden (7); poor caregiver adjustment 3; and poor caregiver quality of life (3).…”
Section: Negative Outcomesmentioning
confidence: 99%
“…Established in 1984 to provide a state-wide specialist service to families and professionals across Victoria, the Bouverie ABI team aims to empower those affected through providing an understanding about the complex nature of acquired brain injury for the person and family members, provide information about resources and services, acknowledge the permanency of the disability, bear witness to the grief and trauma, and draw on family strengths and abilities. Families are offered family therapy as well as opportunities to meet with other families in similar situations (Butera-Prinzi, Charles, Heine, Rutherford, Lattin, 2010).…”
Section: Our Work Contextmentioning
confidence: 99%
“…By bringing families together who share similar challenges, we create a context where families can bear witness to each other's experiences and feel less isolated and personally responsible for difficulties post-ABI. Since 2009, we have been supporting families we see in therapy to meet with each other to share their difficulties and wisdoms of living with acquired brain injury through the Family-to-Family Link-Up program (Butera-Prinzi et al, 2010). In 2010, we began using the Tree of Life as part of this program.…”
Section: Sibling Relationsmentioning
confidence: 99%
“…For family support programmes, capacity building means first and foremost the provision of relevant and practical materials and skills that can be implemented independently by participants. Butera-Prinzi et al (2010) found that the acquisition of knowledge, envisioning of a positive future and the development of advocacy skills by parents were pivotal capacity-building resources. Other studies also demonstrate the significant benefits of building interconnections and peer networks among families as a form of capacity building in terms of sharing of information and experiences leading to greater empowerment (Black et al, 2008).…”
Section: Introductionmentioning
confidence: 99%